2003
DOI: 10.1007/s10227-002-0134-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Infliximab, an Anti-Tumor Necrosis Alpha Antibody, for Inflammatory Dermatoses

Abstract: Infliximab was well tolerated in most patients and the majority benefited from the use of infliximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…In a later step of the cascade, tumor necrosis factor α may also play a role in EF. Indeed, Drosou et al [39] used infliximab, a monoclonal antibody against tumor necrosis factor α, with encouraging effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later step of the cascade, tumor necrosis factor α may also play a role in EF. Indeed, Drosou et al [39] used infliximab, a monoclonal antibody against tumor necrosis factor α, with encouraging effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime steroid therapy is indicated [13] to prevent symptoms such as joint contractures and carpal tunnel syndrome. Nonresponders and patients with contraindications for corticosteroids have been treated with different therapies which have all been reported to lead to improvement alone or in combination, such as antihistamines (hydroxyzine) [9], histamine 2 antagonists (cimetidine) [10, 16, 63], nonsteroidal antirheumatic drugs (ibuprofen) [10], hydroxychloroquine [11], extracorporeal or bath photochemotherapy [12, 13], cytostatics [4, 6, 64] and immunosuppressive agents [39, 65, 66]. Recently some in vitro data have suggested the use of α-interferon in EF, which could inhibit IL-5 production [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 6 patients with recalcitrant PRP were treated successfully with infliximab, an anti-TNF-α monoclonal antibody. Drosou et al [18] reported on 3 patients with PRP who received 2 infliximab infusions at a dose of 5 mg/kg, resulting in a marked improvement of >75%. The treatment was well tolerated without any adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search about the treatment of NL with biological agents returned 6 previously reported cases in the English-language literature [19,20,21,22,23,24]. Clinical characteristics are summarized in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Etanercept (a dimeric fusion protein) and infliximab (a humanized monoclonal antibody) both bind soluble and transmembrane-bound TNF-α and inhibit the TNF-α inflammatory cascade [15,16,17]. The reported response of NL to pentoxifylline [18], a partial TNF-α inhibitor, indicated a possible role of this cytokine in this disease and prompted some authors to initiate anti-TNF-α therapy in treatment-resistant NL [19]. …”
Section: Discussionmentioning
confidence: 99%